Education and training as alternatives to improve human resource skills in the development of Malaysian halal industry - Zakaria, Muhammad Hafeez; Ismail, Mohd Mahadee; Lee, Yok Fee; Mohammad Yusoff, Mohd Haniff; Ab Razak, Ratna Roshida (Secholian Publication, 2022)
HDC aims for as many as 50,000 companies to successfully obtain halal certification in 2030. However, currently, HDC is facing challenges when there are still many companies that have not obtained halal certification. This development shows the need for a strategy that can be implemented to improve human resource skills in the development of Malaysia's halal industry. Therefore, this study was carried out through qualitative methods through interviews and literature review to examine the role of education and training in improving human resource skills in the development of the Malaysian Halal industry. Interviews were conducted with the Halal Hub Division of the Department of Islamic Religion Malaysia and HDC. The results of the interviews are supported by literature research, which is analyzing books, academic journal articles, working papers, websites, statistics, documents, and newspaper clippings. The results of the study found that JAKIM's Halal Hub Division and HDC play a role by providing education and training in improving human resource skills so that players in the halal industry such as companies, government agencies, and consumers involved in the halal industry can further improve their knowledge, performance and the quality of halal products such as marketing, creativity, and product packaging. The aspects of education and training that have been undertaken in developing Malaysia's halal industry are seen to help improve human resource skills in halal development and better management of resources for the production of halal products and services.